Effects of Defoliation at Varying Soil Water Regimes on Aboveground Biomass of Perennial Grasses - Flemmer, Andrea Cecilia (2003)
We evaluated the effects of defoliation under varying soil water regimes on aboveground biomass of perennial grasses native to semiarid rangelands of central Argentina. The palatable species Stipa tenuis and S. clarazii were either defoliated or not for two years within a uniform competitive background of S. gynerioides, an unpalatable species which remained nondefoliated until the end of the study in 1997. Stipa gynerioides increased biomass when soil water was plentiful compared to water stress conditions. This species showed a greater percentage of medium- to large-size plants under rainfed and irrigated conditions than under water stress conditions. Greater shading of S. gynerioides as soil water content increased may have contributed to determine a greater proportion of small-size plants in S. clarazii and of dead plants in S. tenuis in the irrigated than in the water stress treatment. Results suggested that grazing of perennial forage grasses under high soil water contents speeded rather than slowed their degradation when they were competing within a matrix of ungrazed, unpalatable perennial tussock grasses.